The Impact of Intellectual Capital and Islamicity Performance Index on the Financial Performance of Islamic Commercial Banks in Indonesia - Kusuma, Ulfiana Nanda Arni; Atina Shofawati (Universitas Airlangga, 2024)
This study aims to determine the effect of Intellectual Capital and Islamicity Performance Index on Financial Performance proxied by ROA at Islamic Commercial Banks in Indonesia. The research period used is 2016-2022. This research uses a quantitative approach. The population in this study includes Islamic Commercial Banks registered with the Financial Services Authority (OJK) during the 2016-2022 period. The method in this study uses panel data regression analysis techniques with the Random Effect Model (REM) which is chosen as the best model, where the number of observations used is 7 Islamic Commercial Banks selected by purposive sampling method. The results of this study indicate that the variables of Intellectual Capital and Equitable Distribution Ratio partially have a significant effect on Financial Performance. While the variables of Profit Sharing Ratio, Zakat Performing Ratio, and Islamic Income vs Non-Islamic Income have no effect on Financial Performance. All independent variables used in this study simultaneously have a significant effect on Financial Performance.